EDUKASI PELESTARIAN SITUS ARKEOLOGI KUPANG MELALUI KUNJUNGAN SITUS PARTISIPATIF BERBASIS MASYARAKAT - Ukba, Saswal (UI Scholars Hub, 2026)
This community service program aims to introduce and provide education on the preservation of archaeological sites in Kupang City through community-based participatory site visits. Kupang City possesses archaeological remains spanning the prehistoric, colonial, and Japanese occupation periods; however, the extent of scholarly research and preservation efforts remains limited. The program was implemented through field observations, the delivery of historical materials, and interactive discussions conducted at several sites, including Goa Monyet, Fort Concordia, Goa Jepang Liliba, and Bukit Cinta Site. Direct community involvement facilitated a contextual understanding of the significance of cultural heritage and fostered collective awareness regarding its conservation. The results indicate that the site-visit method is effective in enhancing public knowledge and promoting active community participation in the sustainable preservation of cultural heritage.